LINGUISTIC AND EXTRALINGUISTIC PROPERTIES OF COMPRESSION IN THE ASPECT OF FEATURE FILMS - Akhmedova Mushtariybonu Makhmudjonovna (Bright Mind Publishing, 2025)
Translating feature films is a very important and responsible task in the modern world. This translation can be attributed to the commercial type, since it is aimed at the commercial success of the film. The translator in this case acts as an intermediary between the texts in the source language and the target language. The translator can achieve the greatest communicative effect by adapting the title of a work of art or film, taking into account the specific characteristics of the receiving environment, and it is very important that the linguistic and extralinguistic features of compression are correctly used in the translation process.
Keywords: English and Uzbek languages, translation process and theory, compression, linguistic and extralinguistic, films.